A Personalized Approach to Managing Patients With an Ileal Pouch-Anal Anastomosis - Ardalan, Zaid S.; Sparrow, Miles P. (Frontiers in Medicine, 2020)
Quality of life after ileal pouch-anal anastomosis (IPAA) surgery is generally good. However, patients can be troubled by pouch-related symptoms and pouch disorders that can be inflammatory, mechanical/surgical, and functional. Management of patients with IPAA begins with measures to maintain a healthy pouch such as optimizing pouch function, providing tailored advice on a healthy diet and lifestyle, screening for and addressing metabolic complications of IPAA, pouch surveillance, and risk stratification for risk of pouchitis and pouch failure. Pouchitis is the most common inflammatory disorder. Primary pouchitis is a spectrum currently classified into three progressive phases—an antibiotic-responsive, an antibiotic-dependent, and an antibiotic-refractory phase. It is predominately microbially mediated in acute antibiotic-responsive pouchitis and predominately immune mediated in chronic antibiotic-refractory pouchitis (CARP). Secondary prophylaxis is recommended for recurrent antibiotic-responsive and for antibiotic-dependent pouchitis. Secondary causes of antibiotic-refractory pouchitis should be ruled out before a diagnosis of CARP is made. CARP is best classified as primary sclerosing cholangitis associated, immunoglobulin G4-associated, and autoimmune. Primary sclerosing cholangitis-associated CARP can be treated with budesonide or oral vancomycin. Early recognition of immunoglobulin G4-associated pouchitis minimizes ineffective antibiotic use. Autoimmune CARP can be managed in a manner similar to UC. The current place of immunosuppressives in the treatment algorithm depends on availability and early access to biological agents. Vedolizumab and ustekinumab are the preferred first- and second-line biologics for autoimmune CARP owing to their efficacy, better side effect profile, and low immunogenicity and need for concomitant immunomodulatory therapy. Antitumor necrosis factor should be reserved for autoimmune CARP failing the above and for CD of the pouch. There are no guidelines for the surveillance of pouches for dysplasia. Incidence varies based on a patient's risk. Since incidence is low, a risk-stratified approach is recommended.